The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s10815-021-02070-y
|View full text |Cite
|
Sign up to set email alerts
|

Live birth achieved despite the absence of ejaculated spermatozoa and mature oocytes retrieved: a case report

Abstract: The most common reason for in vitro fertilization (IVF) cycle cancelation is a lack of quality gametes available for intracytoplasmic sperm injection (ICSI). Here we present the successful fertility treatment of the couple affected by obstructive azoospermia combined with suboptimal response to controlled ovarian stimulation. Since the conventional approach appeared ineffective to overcome both partnersˈ specific problems, the targeted interventions, namely, (1) pharmacological enhancement of sperm motility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Ebner et al reported that when frozen/thawed testicular sperm samples from TESE were treated with theophylline, sperm motility improved in most cases, and the clinical pregnancy rate increased from 23% to 53% [ 45 ]. The positive effect of theophylline on sperm motility has also been demonstrated in other studies [ 62 , 63 ]. Although there is concern that motility-enhancing chemicals may have toxic effects on embryo development [ 64 ], no evidence of anomalies in offspring has been shown for either theophylline or pentoxifylline [ 63 , 65 ].…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsisupporting
confidence: 77%
“…Ebner et al reported that when frozen/thawed testicular sperm samples from TESE were treated with theophylline, sperm motility improved in most cases, and the clinical pregnancy rate increased from 23% to 53% [ 45 ]. The positive effect of theophylline on sperm motility has also been demonstrated in other studies [ 62 , 63 ]. Although there is concern that motility-enhancing chemicals may have toxic effects on embryo development [ 64 ], no evidence of anomalies in offspring has been shown for either theophylline or pentoxifylline [ 63 , 65 ].…”
Section: Processing and Selection Of Surgically Retrieved Sperm For Icsisupporting
confidence: 77%